2015
DOI: 10.1111/bjd.14031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of atopic dermatitis using self-report and caregiver report: a multicentre validation study

Abstract: Self- and caregiver-reported diagnosis of eczema ever or in the past year based on a single question demonstrates sufficient validity for the epidemiological study of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
101
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 18 publications
6
101
1
Order By: Relevance
“…The results of this study confirm and expand on previous studies that found less self-reported vigorous physical activity among adults with AD from 2 different cohorts (7). In that study, however, physical activity was assessed by self-report, which may not be a reliable predictor of activity levels.…”
Section: To the Editorsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study confirm and expand on previous studies that found less self-reported vigorous physical activity among adults with AD from 2 different cohorts (7). In that study, however, physical activity was assessed by self-report, which may not be a reliable predictor of activity levels.…”
Section: To the Editorsupporting
confidence: 90%
“…History of AD was self-reported and not assessed clinically or verified with any diagnostic testing. However, we previously validated the question used in this study and found it to have very good specificity and positive predictive value (7). Nevertheless, the validation study was performed in the dermatology setting and may not be representative of the US population.…”
Section: To the Editormentioning
confidence: 77%
See 1 more Smart Citation
“…Additionally, a recent validation study found that asking adults, “Have you ever been told by a doctor or other health professional that you had eczema or any kind of skin allergy?” (a question similar to the one used in NHS2), had low sensitivity (0.43) but very high specificity (0.97) for AD. (15) As such, we may have underestimated the true lifetime prevalence of AD. In previous studies, factors associated with adult recall of childhood AD include having eczema after age 15, taking sick leave of more than 1 week due to eczema, long duration of AD in childhood, hand dermatitis as an adult and comorbid atopic disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent multicenter validation study of the eczema question used in the NHIS found good sensitivity, specificity, and positive and negative predictive values. 8 Moreover, self-report of asthma has been previously validated. 9 Thus, I believe that the case definitions for allergic disease are sufficiently valid for epidemiological study.…”
mentioning
confidence: 99%